Single-dose protection against Plasmodium berghei by a simian adenovirus vector using a human cytomegalovirus promoter containing intron A. - Sridhar, S; Reyes-Sandoval, A; Draper, S; Moore, A; Gilbert, S; Gao, G; Wilson, J; Hill, A (2008)
Human adenovirus serotype 5 (AdH5) vector vaccines elicit strong immune responses to the encoded antigen and have been used in various disease models. We designed AdH5 vectors expressing antigen under the control of a human cytomegalovirus (HCMV) immediate-early promoter containing its intron A sequence. The transcriptional levels of antigen and immune responses to antigen for vectors with the HCMV promoter with the intron A sequence (LP) were greater than those for AdH5 vectors using the HCMV promoter sequence without intron A (SP). We compared an E1E3-deleted AdH5 adenoviral vector, which affords more space for insertion of foreign sequences, and showed it to be as immunogenic as an E1-deleted AdH5 vector. Neutralizing antibodies to AdH5 limit the efficacy of vaccines based on the AdH5 serotype, and simian adenoviral vectors offer an attractive option to overcome this problem. We constructed E1E3-deleted human and simian adenoviral vectors encoding the pre-erythrocytic-stage malarial antigen Plasmodium berghei circumsporozoite protein. We compared the immunogenicity and efficacy of AdC6, a recombinant simian adenovirus serotype 6 vector, in a murine malaria model to those of AdH5 and the poxviral vectors MVA and FP9. AdC6 induced sterile protection from a single dose in 90% of mice, in contrast to AdH5 (25%) and poxviral vectors MVA and FP9 (0%). Adenoviral vectors maintained potent CD8(+) T-cell responses for a longer period after immunization than did poxviral vectors and mainly induced an effector memory phenotype of cells. Significantly, AdC6 was able to maintain protection in the presence of preexisting immunity to AdH5.